Keanekaragaman Jenis Makroalga di Pantai Afuik, Desa Dualaus, Kabupaten Belu - Agnes Manewalu; Yoseph M. Laynurak; Gaudensius U.U.B. Duhan (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Afuik Beach, Dualaus Village, Belu Regency, is a coastal area that has the potential for macroalgae biodiversity. This research was conducted to determine the species richness, diversity, and utilization of macroalgae by the local community. The research was conducted in February–March 2025 using the line transect method with 20 transect lines of 25 m in length and a questionnaire survey to the community. Data were analyzed quantitatively using diversity, richness, dominance, uniformity, abundance and Importance Value Index indices, while qualitatively based on questionnaire results. The research results found nine types of macroalgae from three divisions: Chlorophyta (Caulerpa racemosa, C. sertularoides, Halimeda opuntia, H. cuneata, Boergesenia forbesii), Phaeophyta (Sargassum binderi, Padina gymnospora, Turbinaria ornata), and Rhodophyta (Gracilaria coronopifolia). The total number of individuals obtained was 836 with the dominance of Sargassum binderi (364 individuals). The diversity index value (H’=1.54) is classified as moderate, the richness index (1.18) is low, the dominance index (0.287) is low, the evenness index (0.171) is small, the total abundance index (0.176 ind/m2), and the highest INP (70.87). The questionnaire results showed that the community only uses G. coronopifolia as a local vegetable (“Gama/Kama”), with limited economic contribution. Each type found has different characteristics and benefits, the quality of the water also has a great influence on diversity so that the quality of a suitable water environment is a determining factor for the growth and development of macroalgae.